A new Polymixis (Lepidoptera, Noctuidae) species from China - Saldaitis, Aidas; Benedek, Balázs; Babics, János (Zootaxa, 2015)
A new Polymixis Hübner species from China’s Yunnan and Sichuan Provinces is described and distribution data for Polymixis albiorbis Hreblay & Ronkay, 1998 is provided. The type specimen of Polymixis albirena (Boursin, 1944) and the Polymixis magnirena (Alphéraky, 1892) holotype’s genitalia are illustrated.